Atypical presentation in adults in the largest community outbreak of leishmaniasis in Europe (Fuenlabrada, Spain). (March 2015) - Horrillo, L.; San Martín, J.V.; Molina, L.; Madroñal, E.; Matía, B.; Castro, A.; García-Martínez, J.; Barrios, A.; Cabello, N.; Arata, I.G.; Casas, J.M.; Ruiz Giardin, J.M.
Abstract: Since 2009, the largest reported outbreak of leishmaniasis by Leishmania infantum in Europe was reported in Fuenlabrada, Spain. In our hospital, 90 adults with localized leishmanial lymphadenopathy (LLL) or visceral leishmaniasis (VL) were treated during this outbreak; 72% were men, and the mean age was 46.2 years (range 15–95 years). A total of 17 cases (19%) were LLL, an atypical form with isolated lymphadenopathies without other symptoms. All LLL cases occurred in immunocompetent subjects, and only one subject (6%) was a native of sub-Saharan Africa. Diagnosis was performed by fine needle aspiration cytology of the lymphadenopathy. Serology was negative in 38%. LLL outcomes at 6 months were benign, even with doses of liposomal amphotericin B that were often lower (10 mg/kg) than those recommended for VL in Mediterranean areas. A total of 73 subjects (81%) presented with typical VL; 66% of this group were immunocompetent, and 50% of those who were immunocompetent were descendants of natives of sub-Saharan Africa. The rK39 test and polymerase chain reaction were the most useful tests for confirmation of the diagnosis. An initial response to treatment was observed in 99% of cases, and relapses occurred in 14% of cases. Leishmaniasis should be included in the differential diagnosis of isolated lymphadenopathies in endemic areas. LLL could be considered a more benign entity, one different than VL, and less aggressive management should be studied in future investigations.